Model of Decision to Choose a Private Higher Education on Accreditation, Brand Image and Integrated Marketing Communication with Trust as a mediating variable - Laksono, Rudi; Nandan Limakrisna; Anoesyirwan Moeins (Green Publisher, 2024)
Private Higher Education is an alternative choice for students in continuing their education to the next level. Various variables such as university accreditation, brand image and integrated marketing communications are considered by students in making their choices. The purpose of this study was to identify and analyze the effect of accreditation on trust, the effect of brand image on trust, the effect of integrated marketing communications on trust, and the effect of accreditation, brand image and integrated marketing communications on trust, the effect of accreditation on the decision to choose a private university, the effect of brand image on the decision to choose a private university, the effect of integrated marketing communications on the decision to choose a private university, the effect of trust on the decision to choose a private university and the effect of accreditation, brand image, integrated marketing communications and mutual trust on the decision to choose a private university . The theory used in this review paper is Service Dominant Logic (SDL) is a marketing concept formulated by Stephen L. Vargo and Robert F. Lusch in 2004. According to Vargo and Lusch, SDL replaces the goods-dominant logic) centered on the exchange of physical goods with a service-dominant logic focused on value exchange and value creation through customer engagement. In SDL, marketing is defined as a social and economic process in which value is created through interaction between service providers and customers. The dimensions of the student's decision to choose are explained by Hadiyati (2016) Consists of Attention, Interest, Desire and Action (AIDA). Modern marketing theory can be shown in the AIDA Model is the basis of marketing, movement, organizing advertisements resulting from customer perceptions. AIDA explains that in building an effective communication program, the most important aspect is understanding the process by which consumers respond, for example when consumers make purchases at a certain products and services, it is necessary to understand the promotional efforts that can influence the consumer's response.